PENGETAHUAN GIZI, KELUHAN KESEHATAN, KONDISI PSIKOLOGIS, DAN POLA PEMBERIAN ASI IBU POSTPARTUM - Armina Puji Utari; Katrin Roosita; M. Rizal M. Damanik (Food and Nutrition Society of Indonesia, 2013)
This study was aimed to assess nutritional knowledge, health complaints, psychological conditions, and their association with breastfeeding pattern on postpartum mother. A cross sectional study with interview method was conducted in five villages in Dramaga Subdistrict, Bogor District, during the period of April to May 2013. Subjects included in this study were 30 postpartum mothers who met inclusion criteria. Subjects were mothers of 10—40 days old newborn baby and it was not the first childbirth, willing to be subject through informed consent agreement, and was able to communicate. The majority of postpartum mothers had fair nutritional knowledge (60.0%), low health complaints (66.7%), and depression (56.7%). The nutritional knowledge of exclusive breastfeeding tended to correlate with exclusive breastfeeding practice (r=0.126; p=0.508). Meanwhile, lower health complaints tended to correlate with better breastfeeding practices (r=0.063; p=0.74).